A Standard Protocol for the Clinical Management of Suicidal Thoughts and Behavior: Implications for the Suicide Prevention Narrative - David Rudd, M.; Bryan, Craig J.; Jobes, David A.; Feuerstein, Seth; Conley, David (Frontiers in Psychiatry, 2022)
The last several decades have witnessed growing and converging evidence from randomized controlled trials (RCT’s) that an identifiable set of simple clinical management strategies are effective for those at risk for suicidal thinking and/or suicide attempts. The current article offers a brief review of clinical strategies supported by RCT’s targeting suicidality as “commonalities of treatments that work” and related clinical recommendations for their use in the delivery of care for suicidal individuals in generic fashion, regardless of any particular treatment, theoretical orientation, or intervention perspective. The article includes eight specific recommendations that can be easily adapted across the full range of clinical contexts, institutional settings, and delivery systems, recommendations that help frame the broader national narrative for suicide prevention. Clinical recommendations cut across five identifiable domains: 1) informed consent discussion that identifies risks of opting out of care and emphasizes the importance of shared responsibility and a collaborative process, 2) an explanatory model that emphasizes the importance of individual self-management skills and targeting the causes of suicide rather than describing suicidality as a function of mental illness, 3) the importance of proactively identifying barriers to care and engaging in targeted problem-solving to facilitate treatment adherence, 4) a proactive and specific plan for management of future suicidal episodes, and 5) reinforcing the importance of taking steps to safeguard lethal means and facilitate safe storage of firearms.